Perbandingan Representasi Ketidaktstabilan Negara dalam Film Ditto ‘동감’ dan Remakenya: Kajian Semiotika: Perbandingan Ketidakstabilan Negara dalam Film ‘Ditto '동감’' dan Remakenya: Studi Semiotik - Widya Sekarwati; Velayeti Nurfitriana Ansas; Jayanti Megasari (Language Development Center, 2025)
Background: This research discusses the comparison of the representation of state instability in the 2000 film Ditto '동감' with its national remake film Ditto '동감' (2022). The interesting point is there are many studies that have analyzed remake films, but few discuss about national remake films. Purpose: This research aims to fill the research gap by specifically highlighting the comparison of representation in national remake films, between film Ditto '동감' (2000) and its remake film Ditto '동감' (2022), especially on the phenomenon of state instability. Method: Through a qualitative method using John Fiske's semiotic theory, this research analyzes the differences in signs and symbols used by the two films in representing the phenomenon of state instability. The data used are audio, visual, and verbal elements in both films. Results and Discussion: This research shows that although national remake films are remade in the same country that relatively has the same culture and ideology, what and how a phenomena is represented can be very different. This is because representation has no definite standard and is highly dependent on the filmmaker. Conclusions and Implications: The instability of the country in the 2000 film Ditto '동감' is mostly represented through visual elements in the form of news and scenes with minimal dialogue. Meanwhile, the instability of the country in the remake of Ditto '동감' in 2022 is more likely to be represented verbally through dialogue. This research is expected to contribute to the study of semiotics in film, especially intramedium national remake films and aims to be used as teaching materials for Korean language education students to help develop an understanding of semiotics in Korean national remake films.